Technical considerations in designing haptic applications: A case study of laparoscopy surgery simulation with haptic elements - Abdul Rawi, Norkhairani; Zaman, Halimah Badioze; Ahmad, Azlina (Universiti Utara Malaysia Press, 2014)
Simulation has been widely used as a tool for training, especially in high risk areas such as in the aerospace, military and medical fields. Surgery is one of the sub areas that has been receiving much attention from researchers due to the ability of simulation to provide a real surgery setting and human organs with appropriate devices to increase the realism. Developing a surgical simulation is a technically complex process since it involves a few components that interact with each other.Thus this necessitates further considerations regarding the issues and challenges in order to produce an accurate and interactive application.Therefore there is a need for a technical solution framework to help a new and novice researcher in this area to get started. This paper discusses the important components of a surgical simulator, together with its issues and challenges.A proposed solution framework, together with the programming or application choices that are available for each of the components, is explained clearly as concluded from the discussion in the previous work.The class structure for the components is shown briefly to give the new researcher an idea of it.It is hoped that this paper will serve as a foundation for new and novice researchers in haptic development specifically and visual informatics generally.